On the Fourth Power Mean of the Two-Term Exponential Sums - Han Zhang; Wenpeng Zhang (The Scientific World Journal)
The main purpose of this paper is to use the analytic methods and the properties of Gauss sums to study the computational problem of one kind fourth power mean of two-term exponential sums and give an interesting identity and asymptotic formula for it.